1980
DOI: 10.1111/j.1529-8817.1980.tb03016.x
|View full text |Cite
|
Sign up to set email alerts
|

SUBCELLULAR LOCALIZATION OF BROMINATED SECONDARY METABOLITES IN THE RED ALGA LAURENCIA SNYDERAE1

Abstract: Energy dispersive X‐ray fluorescence spectroscopy of thin sections of Laurencia snyderae Dawson shows bromine is concentrated in a cytoplasmic vesicle, the corps en cerise, a previously described structure characteristic of this genus. The presence of the brominated natural product β‐snyderol is shown to be related to the presence of corps en cerise in cortical cells. The presence of halogenated sesquiterpenoids in the corps en cerise of various Laurencia species is inferred from these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
5

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 6 publications
3
48
0
5
Order By: Relevance
“…There is presently no direct evidence to support this hypothesis, since it is only known in a few cases where natural products are biosynthesized within algal thalli. 81 ' 101 ' 104 The carbon-nutrient balance hypothesis (CNBH), proposed by Bryant et al 105 to explain how resource availability affects the phenotypic expression of chemical defenses, suggests that the allocation of resources to chemical defenses will change as environmental conditions such as light or nutrient availability change. For example, when nutrient levels are low and restrict growth, increases in light levels result in excess carbon that can be used for production of carbon-based secondary metabolites.…”
Section: Macroalgaementioning
confidence: 99%
“…There is presently no direct evidence to support this hypothesis, since it is only known in a few cases where natural products are biosynthesized within algal thalli. 81 ' 101 ' 104 The carbon-nutrient balance hypothesis (CNBH), proposed by Bryant et al 105 to explain how resource availability affects the phenotypic expression of chemical defenses, suggests that the allocation of resources to chemical defenses will change as environmental conditions such as light or nutrient availability change. For example, when nutrient levels are low and restrict growth, increases in light levels result in excess carbon that can be used for production of carbon-based secondary metabolites.…”
Section: Macroalgaementioning
confidence: 99%
“…The intracellular refractile inclusion known as Corps en cerise (cherry body) that is usually observed in superficial cortical and trichoblast cells of Laurencia species is a good example. Corps en cerise is recognized as a site for the synthesis or storage of halogenated molecules, 178,402,403 and it was reported that Laurencia species without Corps en cerise do not produce halogenated metabolites. 116 It was also reported that most species in the genus Laurencia produce at least one compound that is not found from any of the others.…”
Section: Chemotaxonomic Significancementioning
confidence: 99%
“…Kumausyne (403) was selected as the most important target compound for the synthesis of tetrahydrofuran-containing ACGs and many research groups have reported elegant strategies/methodologies for the synthesis of this compound (Table 4). 434,456−463 In 1991, Overman and coworkers accomplished the landmark total synthesis of (±)-trans-kumausyne (403). Starting from (1R*,2S*)-1-vinylcyclopentane-l,2-diol (403a), the synthetic sequence afforded (±)-403 in 15 steps and 2.7% overall yield, and employed a novel Prins cyclization-pinacol rearrangement for elaborating the tetrahydrofuran core (Scheme 9).…”
Section: Synthesis Of C 15 -Acetogenins (Acgs)mentioning
confidence: 99%
“…Laurencia species produce bromine-containing compounds in much larger numbers than either chlorine-or iodine-containing ones whereas, the Clcontaining compounds usually also possess Br atom(s) [6]. A large number of these compounds have been obtained from Laurencia species having an intracellular, membrane-bound vesicles known as "corps en cerise" (cherry bodies) in the outer cell layer (the cortical layer) where, these inclusions are considered as a synthesis and/or storage sites of halogenated secondary metabolites [7]. On the other hand, Laurencia species without "corps en cerise" does not produce any halometabolites [8].…”
Section: Introductionmentioning
confidence: 99%